Estudo de haplótipos da globina ΒS com o fator de crescimento endotelial vascular (VEGF), hemoglobina fetal e eventos clínicos em pacientes com anemia falciforme - Galvão, Lívia Monteiro (2016)
Sickle cell anemia (SCA) is a hereditary disease caused by a point mutation in βS globin gene causing an abnormal hemoglobin called hemoglobin S (HbS), when deoxygenated polymerizes favoring the vaso-occlusion phenomenon, vascular endothelial injury and expression of angiogenic factors. Genetic factors such as beta globin S haplotypes are responsible for the clinical differences among patients. The aim of this study was to investigate the association of haplotypes of βs globin with vascular endothelial growth factor-A (VEGF-A), with fetal hemoglobin (HbF) and clinical manifestations in patients with SCD. The study was cross, analytical and observational. The study population consisted of 51 patients with a molecular diagnosis of SCD, 39 in use hydroxyurea (HU) (617 mg/day) and 12 unused. A total of 61 individuals without hemoglobinopathies, considered healthy, participated as a control group. The haplotype analysis was performed by PCR-RFLP and the dosage of VEGF-A by ELISA. Clinical and laboratory data were obtained in consultation records. Statistical analysis was performed by using the statistical program GraphPad Prism version 5.0. Patients with SCD showed characteristic hematological disease and significant increase in VEGF-A in the control group when stratified patients by the use of HU was observed higher concentrations among patients who were not in use HU. The predominant haplotype in the group studied was the Bantu, there was no difference in VEGF-A concentrations between groups of haplotypes of βS globin and clinical manifestations, except for the vaso-occlusive crises (CVO), where the use of HU influenced VEGF-a concentrations in the group with the largest number of attacks per year. There was a negative correlation between VEGF-A concentrations and concentrations of HbF and a positive correlation with the reticulocyte count. It is concluded that the increase of VEGF-A in patients without use of HU can be attributed to the pathophysiology of disease and probably the use of HU had an anti-angiogenic effect. However more studies are needed to evaluate the role of VEGF-A and angiogenesis in SCD.